ANALISIS MAKRO EKONOMI, PROFIL RISIKO TERHADAP KINERJA PERUSAHAAN DAN NILAI PERUSAHAAN PADA BANK UMUM YANG TERDAFTAR DI BURSA EFEK INDONESIA - Febrianto, Gustaf Naufan (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2020)
The purpose of this study is to examine the Analysis of macro economy, risk profile, to firm performance and value of the firm in Coomercial Banks go public listed in Indonesia stock exchange. The sample used in this research is 44 companies with 3 years observation from 2017-2020 This study uses a qualitative descriptive research design. The population in this study is the Public Foreign Exchange Commercial Bank Companies listed on the IDX. Thus the number of samples in this study were 44 banking companies listed on the IDX. The results showed: Macroeconomic impact on company performance at the National Public Bank Foreign Exchange, Macroeconomic affects the value of the company on the National Public Bank Foreign Exchange Go Public, Risk Profile impacts on company performance at the Go Public National Bank, Risk Profile impacts on company value of the company at the National Public Bank Go Public Financial Performance affects the value of the company at the National Public Bank Foreign Exchange Go Public